Unusual Case of HIT With Cardiac Arrest During Hemodialysis. (August 2014) - Grandvuillemin, Aurélie; Zanetta, Gilbert; Perrin, Julien; Amiral, Jean; Elalamy, Ismail; de Maistre, Emmanuel
Objective: To report an unusual case of heparin-induced thrombocytopenia (HIT) with cardiac arrest during hemodialysis (HD).Case Summary: An 88-year-old man previously treated with HD under enoxaparin for 3 years presented with dizziness and cyanosis at the beginning of HD on 3 consecutive sessions. Even though the dialyzer membrane was changed, he presented with cardiac arrest, from which he recovered quickly. At the same time, the platelet count fell, and HIT was suspected. No thrombosis was found. Anti-PF4/H, IL8, and NAP2 antibodies were negative, but platelet aggregation tests and serotonin-release assay were positive. After implementing HD with danaparoid, the platelet count returned to normal, and the patient remained asymptomatic.Discussion: Given the clinical context (low-molecular-weight heparin), complications (cardiac arrest and no thrombosis), and timing (3 years), this was an unusual case of HIT. According to the Naranjo probability scale, the causality of enoxaparin was evaluated as probable. In most reported cases, time to onset was short, clotting occurred in the extracorporeal system, and biological tests, including ELISA (enzyme-linked immunosorbent assay) anti-PF4/heparin, were positive. We found no triggering factor in this case, and given the biological results, a new antigenic target may be involved.Conclusions: HIT must be considered when acute systemic reactions occur at the beginning of HD sessions, even after several years of HD and with no change of anticoagulant, including low-molecular-weight heparin. The platelet count should be measured immediately after the reaction. The diagnosis is important because of possible cardiac arrest in this context.